UPDATING OF SURAKARTA SEISMIC SITE CLASS MAP BASED ON STANDARD PENETRTION TEST - Yusep Muslih Purwana; Raden Harya Dananjaya; Yusuf Cahyo Nogroho (Prodi Teknik Sipil FT Universitas Sebelas Maret, 2020)
Surakarta is one of the cities in Java island with a high population growth rate, triggering the increase in the construction, especially for high-rise buildings. The city is close to several earthquake sources, causing a high level of seismic hazard. One of the main parameters of earthquake resistant building design is the value of peak ground acceleration at surface level. It is obtained by multiplying the peak ground acceleration in the bedrock by a multiplier factor that depends on the site class conditions of the location. A previous study has been conducted in 2015 using 32 boreholes indicating that around 19.5% of Surakarta area is classified as SC (hard soil), and 80.5% of the rest is SD (medium soil). To increase the accuracy, another 31 additional boreholes data are adopted. The new result shows that Surakarta is divided into three different seismic site class. Around 4.80% the area is classified as SC (hard soil), 94.50% is SD (medium soil), and 0,70% is SE (soft soil). The southern part of Surakarta has a higher level of vulnerability to earthquakes, especially in the border area between Banjarsari, Laweyan, and Serengan subdistricts which have a SE (soft soil) seismic site class.